Adecuación estructural del bloque 2 y de los espacios de interés común dentro de la universidad de la costa, para garantizar el desplazamiento a personas con discapacidades motrices y movilidad reducida (2013)
This thesis aims to describe and analyze the existing situation of the setting-up of the Universidad de la Costa, CUC, and likewise to propose a prototype of structural solutions that significantly improves accessibility standards in the layout of spaces of common interest, so that it will eliminate physical barriers that prevent the free movement of persons in disability status. Although these changes go unnoticed for most users, patently for people with reduced mobility, these will be an increase in their quality of life being that they will get a high degree of autonomy, safety and comfort to arrive and move into the Universidad de la Costa.